2020
DOI: 10.1080/00380253.2020.1787111
|View full text |Cite
|
Sign up to set email alerts
|

Egocentric Contact Networks of Older Adults: Featuring Quantity, Strength and Function of Ties

Abstract: This article analyzes how the theory of constraints, the socio-emotional and functional selectivity theories can explain the egocentric networks of older adults. The contact diary method is applied on a randomly chosen subsample of a nationally representative cross-sectional sample in Hungary enumerating all active ties and encounters with social contacts of 181 adults aged 50 and above. Age is negatively associated with network size, but it is positively correlated with average tie strength. Retirement, decli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 53 publications
0
8
0
1
Order By: Relevance
“…Having a high proportion of strong ties and family ties in a personal network can also be detrimental to forming and mobilising social capital. While strong family ties play a significant role in providing material support ( 24 ), a study of low-income households in Brazil indicated that those with closed networks composed primarily of close relatives tend to be isolated from other households or social units in the community ( 25 ). On the other hand, networks that incorporate a larger proportion of weak ties from more diverse backgrounds may mobilise a larger total amount of social capital ( 21 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Having a high proportion of strong ties and family ties in a personal network can also be detrimental to forming and mobilising social capital. While strong family ties play a significant role in providing material support ( 24 ), a study of low-income households in Brazil indicated that those with closed networks composed primarily of close relatives tend to be isolated from other households or social units in the community ( 25 ). On the other hand, networks that incorporate a larger proportion of weak ties from more diverse backgrounds may mobilise a larger total amount of social capital ( 21 , 25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous research on personal support networks of older adults reports that this population is more likely to have smaller networks with stronger social ties than younger individuals (23)(24)(25). Older adults with greater care needs also tended to have a personal network composed mostly of first-degree relatives, partially explaining the higher prevalence of strong ties within this population (23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contact diary method asks respondents to track and record all their interpersonal contacts (interactions) over a given period. It measures daily contacts directly and comprehensively, reconstructing the components of the personal networks that are active and adequate in everyday life (Albert et al, 2020;Dávid et al, 2016;Fu, 2005Fu, , 2007Huszti et al, 2013;Lukács & Dávid, 2019). Revealing the daily contacts of egos, a contact diary provides information on the size and composition of personal social networks.…”
Section: Contact Diarymentioning
confidence: 99%
“…Voluntary associations better lend themselves to egocentric network designs due to their likelihood of having incomplete member lists and potentially for the informal nature of their association, compared to work organizations engaged in money‐making activities. Much like personal networks, egocentric network designs for voluntary associations start from one focal actor to scope the alters to which he/she is linked, offering a cross‐sectional snapshot of social dynamics in a network (Albert et al., 2021; Friedkin et al., 2019).…”
Section: The Study Of Social Capital Exchanges In Organizationsmentioning
confidence: 99%